In vitro antimicrobial activity of the essential oil from Vanillosmopsis arborea Barker (Asteraceae) and its major constituent, α-bisabolol. (December 2018) - Rodrigues, Fabíola Fernandes Galvão; Colares, Aracélio Viana; Nonato, Carla de Fatima Alves; Galvão-Rodrigues, Fabío Fernandes; Mota, Magaly Lima; Moraes Braga, Maria Flaviana Bezerra; Costa, José Galberto Martins da
Abstract: Vanillosmopsis arborea Barker (Asteraceae), commonly known as "candeeiro" is an endemic tree to the Caatinga biome, in northeast Brazil. The major component of its essential oil is α -bisabolol, a monocyclic sesquiterpene alcohol with several biological activities reported. In this study, the antimicrobial activity of the essential oil of V. arborea was investigated in comparison with its major component α -bisabol. The antimicrobial activity was performed against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 12692, Candida albicans (CA) INCQS 40006, Candida krusei (CK) INCQS 40095, Candida tropicalis (CT) INCQS 40042, and multiresistant bacterial strains Staphylococcus aureus 03 and Escherichia coli 08 by the microdilution method and direct contact modulation. The results showed that all strains were sensitive to the samples, except E. coli against the essential oil. Both the essential oil and the α -bisabolol had a synergistic effect against all strains, except for ampicillin against S. aureus 03, which did not show any modifications when combined with the oil. These data show the potential of V. arborea essential oil as an antibiotic modulator as well as a source of bioactive compounds with potential for the development of antimicrobial drugs as well as adjuvant to therapy against these pathogens. Highlights: Antimicrobial activity of the essential oil of Vanillosmopsis arborea was investigated in comparison with α -bisabol. Antimicrobial activity was performed by the microdilution method and direct contact modulation. Essential oil and the α -bisabolol had a synergistic effect against all strains, except against S. aureus 03. Essential oil of V. arborea proved to be a potential antibiotic modulator.